Development of E-Learning Materials Assisted by Augmented Reality in the Science Subject of Water Cycle Material for Grade V Elementary Schools - Dwika Yafi Muharromi; Novi Setyasto (Postgraduate, University of Mataram, 2025)
This study aims to develop, test the feasibility, effectiveness, and practicality of Augmented Reality (AR)-assisted e-learning materials to improve student learning outcomes. This study is a development research (R&D) using the Borg and Gall model. This study involved 34 fifth-grade students of SDN Dampyak 02 in the 2024/2025 academic year, with a small-scale trial on 12 VA-class students and a large-scale trial on 22 VB-class students. The feasibility of e-learning materials is shown from the results of validation by material, language, and media experts which showed that AR-assisted e-learning materials were declared